(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Teodora-Alina Roșca analyzes Arthur Rimbaud’s A Season in Hell as a transformative linguistic and metaphysical experience. The study explores how Rimbaud’s personal trauma and rejection of traditional poetic imitation lead to an "alchemy of the verb." By descending into a personal, moral, and aesthetic Hell, the poet confronts his inner demons and family tensions. Ultimately, Rimbaud’s "infernal prose" subverts classical rhetoric, celebrating the aesthetics of the ugly and achieving a profound, modern spiritual rebirth. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.